A NON-LINEAR HYPOCENTER LOCALIZATION ALONG THE ACTIVE PALU-KORO FAULT: A CASE STUDY CENTRAL SULAWESI - Jayadi, Harsano; Th. Musa, Moh. Dahlan; Rachman, Gazali; Meidji, Icha Untari; Massinai, Muhammad Fawzy Ismullah; Warnana, Dwa Desa (Indonesian Physical Review, 2025)
The Central Sulawesi region is prone to earthquakes, as evidenced by its complex geological structure. Several plates and active fault movements in the vicinity cause this situation. One of the active faults that often causes earthquakes is the Palu-Koro active fault. The city of Palu is one of the areas passing through the Palu-Koro fault. The danger of this earthquake occurrence can be ascertained and assessed using a suitable earthquake location. Within the scope of our investigation, we used a non-linear approach to predict the hypocenter site in the vicinity of the Palu-Koro fault that is active. This Method use oct-tree importance sampling algorithm to generate spatial hypocenter locations. Using the AK135 minimal seismic velocity model, we manually re-picked the arrival times of wave P-waves and S-waves arrival timings of 3,852 and 3,690, respectively, collected by 24 BMKG observation sites from January 2011 to December 2015, utilizing the minimal 1D seismic velocity model from AK135. We employed criteria to ascertain the event's location, including a minimum of four stations exhibiting a distinct beginning of P and S wave arrivals, with a magnitude of at least 3Mw and an average depth ranging from 10 to 20 km. The outcomes of seismic event location identification exhibit improved clustering with inversion, revealing a zero-centered Gaussian distribution, where more time discrepancies, both positive and negative, correspond to increased estimating mistakes. According to this research, the Palu-Koro active fault line's primary shallow seismic zone is the most prominent feature in the area and confirms the existence of active land faults that cause earthquake events by conducting a process of determining a locally updated 1D velocity model that will be used to determine a more precise relocation of the hypocenter used to interpret the subsurface model of the research area.